Pengembangan Modul dengan Lima Permainan Tradisional Guna Mempertajam Hati Nurani Anak Usia 9-12 Tahun - Anna Wijayanti; Gregorius Ari Nugrahanta; Irine Kurniastuti (Universitas Kanjuruhan Malang, 2021)
This research aimed to develop a module with five traditional games for sharpening conscience children 9-12 years old. The type of this research is R&D with ADDIE. This research has done in the region Magelang, Central Java. The result showed the quality of the module with five traditional games was very nice. The validation test 3,72 a very nice category. The implementation of the module with five traditional games has affected children’s conscience. The result of the paired samples t-test the posttest score (M = 85,00, SE = 4,226) was higher than pretest score (M = 46,25, SE = 5,957) and the difference was significant with t = 7,519, p = 0,000. That means the implemented of traditional games’s modul can explain 87,60% of the change in conscience. The effect size showed r = 0,936 has equivalent with 87,60% which into the high category. N-gain score 74,643% high effectiveness.